A lived and living UK gaming oral history: untangling narratives of resistance and resurgence in videogame space - Kaufman, Imo (2025)
This thesis critically examines gaming subjectivities, games culture, and ideologies that circulate within videogames and their communities. Via a series of oral history interviews, and with an emphasis on a person-centred approach, this research scrutinises the bleed between gaming culture and far-right belief systems, evidenced by issues like identity policing and online harassment. However, rather than focusing on the extreme edges of games culture, which movements of organised harassment like Gamergate made overt, this work considers the gaming mainstream and the experiences of ostensibly “normal” people within gaming; what they think, and how they feel, about videogames, gamer identity and games culture.